KONSUMSI ROKOK ORANG TUA SEBAGAI FAKTOR RISIKO KEJADIAN STUNTING PADA ANAK USIA 6 â 24 BULAN DI KOTA YOGYAKARTA - , Siska Puspita Sari, Prof. dr. M. Juffrie, SpAK, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background:Stunting or short is a growth failure with deficits in length for age <-2 z-scores based on standard reference growth of World Health Organization 2005. Stunting is influenced by many factors, including parental smoking. In Yogyakarta coverage of parental smoking are high (52.1%) and the prevalence of stunting toddler reaches 15.11%. Therefore need to be studied parental smoking a risk factors of stunting inchildren aged 6-24 months. Objective: Analyze parental smoking as a risk factor for the incidence of stunting in children aged 6-24 months in the Yogyakarta City. Methods: This study is an observational study with case control study design. The subjects were all children aged 6-24 months were recorded in the register a toddler posyandu in 3 subdistricts (Umbulharjo, Tegalrejo and Kotagede) and his parents live, the study site ofinclusion and exclusion criteria. Number of samples 121 cases and 121 controls. Univariate data analysis, bivariate using Chi-square, and multivariate using multiple logistic regression. Result: This research shows as much as 58,68 % of the childrenwere parents who smoking. Bivariate analysis showed there was no statistically significant association between parental smoking withthe incidence of stunting in children aged 6-24 months in the Yogyakarta City p=0,601